Online monitoring of propofol concentrations in exhaled breath - Xiaoxiao Li; Pan Chang; Wensheng Zhang (Heliyon)
Propofol, a widely used intravenous anesthetic agent, requires accurate monitoring to ensure therapeutic efficacy and prevent oversedation. Recent developments in modern analytical instrumentation have led to significant breakthroughs in on-line analysis of exhaled breath. This review discusses several sophisticated analytical methods that have been explored for noninvasive, real-time monitoring of propofol concentrations, including proton transfer reaction mass spectrometry, selected ion flow tube mass spectrometry, ion mobility spectrometry, and gas chromatography coupled to surface acoustic wave sensors. These techniques have demonstrated good correlations between plasma and exhaled propofol concentrations and between exhaled propofol concentrations and its cerebral effects. Despite these advances, the use of these technologies in clinical settings is hampered by challenges such as equipment noise, bulkiness, and high cost, as well as limitations related to endotracheal intubation, strong adsorption of propofol to components of the respiratory circuit, variability in respiratory patterns, susceptibility to changes in pulmonary ventilation and blood flow, inconsistencies in calibration methods, and the influence of other drugs and temperature fluctuations on measurement accuracy. Overcoming these technical and procedural challenges is critical to advancing the clinical application of breath analysis for propofol monitoring. This article reviews published studies and summarizes the progress and ongoing challenges in the field.